El-Ganzouri multivariate risk index based airway management in head and neck cancer patients: A retrospective analysis of 1000 patients in a tertiary care center - Raghav Gupta; Nishkarsh Gupta; Vinod Kumar; Rakesh Garg; Sachidanand J Bharati; Seema Mishra; Sushma Bhatnagar (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Intubation in head and neck carcinoma (HNC) is difficult due to many reasons. Various guidelines recommend strategies for airway management in such anticipated difficult airway cases. However, literature is limited on airway management planning as per the level of difficulty based on airway assessment in these patients. EL-Ganzouri risk index (EGRI) has been proposed to aid in making airway management plan in HNC cases by some authors. This retrospective study was conducted to look at the data related to the pre-anesthetic airway assessment and the airway management plan executed by the anesthesiologists in 1000 patients of HNC in the previous nearly four years in order to determine how the choices made conformed to EGRI scores. Material and Methods: Records of all the patients with oral cancer posted for surgery over four years from January 2014 to December 2017 were retrospectively analyzed for preoperative airway assessment using El Ganzouri risk index assessment (EGRI), the intraoperative technique for nasotracheal intubation, airway management plan, and any intraoperative complications. Results: The risk of predicted airway difficulty was low (EGRI <4) in 38 patients and was high in the rest. The EGRI score was higher in the FOB group [4-9] as compared to DL [2-3] and VL [1-6]. The patients with EGRI >7 were intubated awake and those with EGRI <7 were intubated under general anesthesia (79.8%). Overall, the technique of choice for intubation was fibreoptic bronchoscopy (54%) followed by video laryngoscopy (42.6%). Conclusion: The airway management plan used in a tertiary care cancer center conformed to the approach suggested by the multivariate El Ganzouri risk index (EGRI). EGRI appears to be a useful means to ascertain the appropriate strategies for intubation in head and neck cancer patients.